Advanced Crisis Management in Enterprise Networks: An Exploratory Study on the Effects of the Pandemic - Gentili, Luigi (Italian Sociological Review, 2023)
The aim of this article is to show the results of an exploratory study on crisis management in business networks. Using sociological research and the case study methodology, twenty-four questionnaires were handed out to managers of interorganizational networks, representative of the associations they belonged to. These are privileged witnesses, active in the most relevant production sectors. The research was carried out on a national level, region by region. The results describe an evolving business trend. According to the respondents, business networks are more efficient when dealing with a crisis. Flexibility, mutual support and territorial roots are the assets that make enterprise networks more competitive. By examining the data we can devise a new socializing practice, carried out in a structure with shared organization. According to the research findings, the identity dimension of business networks needs a deeper understanding. Network branding is a step in that direction. The correlation between network branding and Industry 4.0 policies, another important factor that emerges from the research results, allows us to create a matrix with four styles of crisis management. Together they make up a map of networks management, classified according to the response given to the current pandemic crisis. The advanced crisis management style in the matrix described in this article is an emerging form of inter-firm coordination.